The impact of corporate governance structure on commercial banks' profitability in China - zhou, qimin (2019)
Abstract The concept of corporate governance gradually received much more attention in the past decades. The main reason why researchers turn their eyes to the new area of corporate study is that it is found to be one of the main causes of corporate scandals and failures. Especially after the financial crisis in 2008, when studying the causes of the crisis, researchers found that corporate governance structure played a significant role in promoting the cause of the crisis. Therefore, more and more scholars take corporate governance as their research topic. This paper takes the influence of corporate governance on the profitability of commercial banks as the research object, and in this paper, 32 Chinese Listed Commercial Banks come from Shanghai Stock Exchange, and the time span of data is from 2008 to 2018. As a major contributor to China's economy and an entity maintaining economic and financial stability, it is very important for banks to understand the role of corporate governance on performance. The focus of the study is to find out the impact of corporate governance on the financial performance of banks. For this purpose, independent variables are indicators to measure corporate governance obtained by reading and summarizing relevant literature. The financial performance indicator used is a return on assets. This paper examines the relationship between corporate governance and listed banks in China by establishing a multiple linear regression model. The results show that the relationship between the two is consistent with the hypothesis in this paper; that is, corporate governance helps to improve the banks’ profitability in China. Accordingly, this paper puts forward corresponding countermeasures suitable for improving the profitability of listed commercial banks in China.